2018
DOI: 10.4103/1673-5374.237125
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for accuracy of pain assessment and painkillers utilization in neuropsychiatric symptoms of dementia in Calabria region, Italy

Abstract: During the clinical course of dementia, beside cognitive impairment and memory loss, a very complex challenge is posed by the neuropsychiatric symptoms (NPSs). Accurate evaluation and treatment of pain impacts positively the agitation of demented patients aged ≥ 65 years. To gather information on the utilization of pain killers in demented patients a preliminary survey has been conducted in collaboration with the Calabrian Pharmacovigilance Territorial Service of the health district of Catanzaro (Italy). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Indeed, all the included studies were quite old and dating prior to the 2009 CPSP redefinition (Klit et al, 2009), which made the differential diagnosis between CPSP and other types of post-stroke pain clearer and more reliable. Pain assessment represents an important issue in non-communicative patients, who can have difficulties to describe their pain, contributing to behavioral disturbances in some neurological conditions (Scuteri et al, 2017;Scuteri et al, 2018;Scuteri et al, 2019a;Scuteri et al, 2019b). Indeed, in the real-life clinical setting, the use of opioids in patients with post-stroke pain, who are not able to communicate is frequent, but the response to treatment is unclear (Schuster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, all the included studies were quite old and dating prior to the 2009 CPSP redefinition (Klit et al, 2009), which made the differential diagnosis between CPSP and other types of post-stroke pain clearer and more reliable. Pain assessment represents an important issue in non-communicative patients, who can have difficulties to describe their pain, contributing to behavioral disturbances in some neurological conditions (Scuteri et al, 2017;Scuteri et al, 2018;Scuteri et al, 2019a;Scuteri et al, 2019b). Indeed, in the real-life clinical setting, the use of opioids in patients with post-stroke pain, who are not able to communicate is frequent, but the response to treatment is unclear (Schuster et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the real-life clinical setting, the use of opioids in patients with post-stroke pain, who are not able to communicate is frequent, but the response to treatment is unclear (Schuster et al, 2020). Post-stroke pain can occur also in patients with neurodegenerative disorders (Scherder and Plooij, 2012) and clinical trials to assess the efficacy and safety of opioids are needed, being the treatment of pain often inappropriate in this population (Scuteri et al, 2017;Scuteri et al, 2018;Scuteri et al, 2020a;Scuteri et al, 2020b). Future double-blind randomized clinical trials designed specifically for poststroke pain, methodology and statistical power are needed to assess the efficacy and safety of opioids in post-stroke pain and to understand the impact of pain treatment on physical function.…”
Section: Discussionmentioning
confidence: 99%
“…The development of NPSs, and of agitation mainly, is linked to misdiagnosed [64,65] and unrelieved pain [66,67]. In fact, the demented patients who are provided with analgesic therapy are less common than the general population [68], thus supporting pain undertreatment that has been also highlighted in the local context [69,70]. It was demonstrated that a stepwise protocol for pain treatment significantly reduced agitation of the 17%, with an increase after withdrawal [71].…”
Section: Novel Pharmacological Mechanisms For Npss Of Dementia CLImentioning
confidence: 99%
“…The development of NPSs, and of agitation mainly, is linked to misdiagnosed [61,62] and unrelieved pain [63,64]. In fact, the demented patients who are provided with analgesic therapy are fewer than the general population [65], thus supporting pain undertreatment that has been highlighted also in the local context [66,67]. It was demonstrated that a stepwise protocol for pain treatment significantly reduced agitation of the 17%, with an increase after withdrawal [68].…”
Section: Novel Pharmacological Mechanisms For Npss Of Dementia Clinicmentioning
confidence: 99%